A study on prevalence of depression in patients of vitiligo in tertiary care centre in South India - Rathi, Sneha R.; Badad, Ambresh S.; Hogade, Ashok S. (International Journal of Research in Dermatology, 2019)
Background: Skin is an organ that has a primary function in tactile receptivity and reacts directly upon emotional stimuli. The effects on the quality of life as a result of acquiring vitiligo is highlighted. Methods: 100 patients with vitiligo were included in this study. A survey was done on the basis of Hamilton score of depression (HAM-D) having 17 different points that were supposed to be asked. Results: The majority of the patients in this study were in 3rd to 5th decade. Mean age is 42 years. Of these, males were 44 and females were 56. Of these, 25 (25%) patients did not show any signs of depression, 45 (45%) patients showed mild depression, 20 (20%) patients showed moderate depression and 10 (10%) patients showed severe depression on HAM-D scale. Conclusions: Vitiligo is a secondary psychocutaneous disorder which definitely has psychiatric co morbidity inthe form of depression. Treatment of vitiligo should include psychiatric counselling along with specific treatment.